Integrating systems and design thinking in transdisciplinary case studies. - Pohl, Christian; Pearce, BinBin; Moder, Marlene; Senn, Lisette; Krütli, Pius (ÖKOM, 2020)
Umweltproblemlösen (Tackling environmental problems) is a Bachelor-level course that carries on a long tradition of transdisciplinary (td) case studies in the Environmental Sciences curriculum of ETH Zurich. Td case studies introduce students to key features of transdisciplinarity. Two corresponding learning goals of the case studies are: 1. to not only analyse problems, but to also suggest solutions, and 2. to take the complexity of the tackled socio-ecological system into account. In the new course we address both learning goals by integrating systems and design thinking. We present this approach in detail to show how features of transdisciplinarity are transferred to learning contexts. We compare it to the approaches of other td case studies by asking how each interprets and addresses the two learning goals. The comparison shows that the case study approaches implicitly impart different ideal about how a td environmental scientist should support societal problem solving. A key difference to previous approaches is that the new course asks students to enter deeply into the world of practice and the stakeholders' divergent needs.
Keywords: Umweltwissenschaft; Studieninhalt; Problemlösung; Lernziel; Praxisbezug; Interdisziplinarität; Fallstudie; Umweltproblemlösen; Umweltnaturwissenschaften; Bachelor-Studiengang